DalROMS-NWA12 v1.0, a coupled circulation–ice–biogeochemistry modelling system for the northwest Atlantic Ocean: development and validation - K. Ohashi; A. Laurent; C. Renkl; J. Sheng; K. Fennel; E. Oliver (Geoscientific Model Development)
This study presents DalROMS-NWA12 v1.0, a coupled ocean circulation–sea ice–biogeochemistry modelling system for the northwest Atlantic Ocean (NWA) in which the circulation and biogeochemistry modules are based on ROMS (Regional Ocean Modeling System). The circulation module is coupled to a sea ice module based on the Community Ice CodE (CICE), and the physical ocean state simulated by the circulation module drives the biogeochemical module. Study of the biological carbon pump in the NWA is one of the main intended applications of this model. Global atmospheric and ocean reanalyses are used to force DalROMS-NWA12 at the sea surface and as part of its lateral boundary input, respectively. The modelling system is also forced by tides, riverine freshwater input, and continental runoff. The physical ocean state and sea ice from two simulations of the period 2015–2018, with and without nudging of the simulated temperature and salinity towards a blend of observations and reanalysis, are examined in this study. Statistical comparisons between model results and observations or reanalyses show that the control (nudged) simulation outperforms the prognostic (un-nudged) simulation in reproducing the paths of the Gulf Stream and the West Greenland Current, as well as propagation of the estuarine plume in the Gulf of St. Lawrence. The prognostic simulation performs better in simulating the sea ice concentration. The biogeochemical module, which is run only in the control simulation, performs reasonably well in reproducing the observed spatiotemporal variations in oxygen, nitrate, alkalinity, and total inorganic carbon. To examine the effects of tides and sea ice on the physical fields in the study area, results of simulations from which either component is absent are compared to results of the prognostic simulation. In the absence of tides, Ungava Bay in summer experiences a simulated surface salinity that is higher by up to ∼7 psu than in the simulation with tides, as well as experiencing changes in horizontal distributions of surface temperature and sea ice. Without coupling to the sea ice module, the circulation module produces summertime sea surface temperatures that are higher by up to ∼5 °C in Baffin Bay.